Kirurško zdravljenje adneksnih tumorjev v nosečnosti - pomen laparoskopskega operiranja - Peternelj-Marinšek, Suzana (Zdravniški vestnik, 2002)
Background. The aim of this retrospective study was to find the incidence and type of adnexal masses in pregnancy, reliability of preoperative ultrasound examination and the effect of the surgical approach used, duration of pregnancy at the time of surgery, and the effect of emergency or planned surgery on the outcome of pregnancy. The obtained results and the data from literature were to provide the basis of the guidelines for the management of pregnant women with adnexal masses. Methods. In the study we enrolled 42 women, who underwent a surgery in pregnancy for adnexal masses. All surgeries were performed at the Department of Obstetrics and Gynecology in the period 1 January 1993 - 31 August 2000. The course of pregnancy was followed by 28 February 2001. The data were obtained from the records kept at the Department and from the questionnaire sent to the women. Statistical analysis was done using Chi-square test. Statistical significance was set at P =< 0.05. Results.We found the incidence of adnexal masses in pregnancy, requiring surgical treatment, to be 1/1034 deliveries. There were 6 (14.3 %) borderline malignant and malignant ovarian tumours, the incidence being 1/7239 deliveries. Preoperative ultrasound examination was not reliable enough to differentiate neither between benign and malignant adnexal masses, nor betweenadnexal masses and leiomyomas. Forty-two surgeries were made, 21 by laparoscopy and 21 by laparotomy. The size of removed tumours ranged between 4and 30 cm (mean 9.4 cm), the most frequent type was mature cystic teratoma (n=12). There were no differences in the outcome of pregnancy between the laparoscopy and laparotomy approach, between emergency and planned surgery, and between laparotomy performed by the 23rd and after the 23rd gestational week. Hemorrhagic shock due to heterotopic pregnancy lead to 1 spontaneous abortion. (Abstract truncated at 2000 characters).
Keywords: Adneksi maternični; Adnexa uteri; Diagnosis; ginekologija; human pregnancy; Izid nosečnosti; Jajčnik, novotvorbe; jajčniki; Laparoscopy; Laparoskopija; Laparotomija; Laparotomy; neoplasm; Nosečnost; Nosečnost, komplikacije neoplastične; Ovarian neoplasms; Pathology; Pregnancy; Pregnancy complications, neoplastic; Pregnancy outcome; Retrospective studies; Retrospektivne študije; Surgery; therapy; tumor; Ultrasonography; zdravljenje